Probiotic effects on tiger shrimp (Penaeus monodon) growth and water-sediment quality of ghers in Bagherhat, Bangladesh (Journal of the Asiatic Society of Bangladesh, Science, 2026)
Probiotics are live microorganisms which enhance shrimp productivity and maintaining favourable water and soil qualities. This study was conducted to ascertain the effect of three probiotics on shrimp growth, feed utilization, survival, water and sediment qualities in coastal ponds of Bagerhat, Bangladesh. Twelve ponds were selected and divided into four treatment groups as T1 (Miracure), T2 (Biozyme), T3 (Rapidgrow) and T4 (control-without probiotics) with same stocking densities of 6 PL/m². Shrimp were feed 30% protein (Mega feed Ltd.) thrice daily at 5-10% of body weight for 120 days. Growth performance, shrimp biomass and feed utilization increased significantly (p